School inclusion and physical infrastructure of elementary school - Santos, Camila Elidia Messias dos (2021)
This paper aimed to verify the conditions of the physical infrastructure of schools in a Municipal Elementary School System, considering the target students of Special Education. The design used was the qualitative of the descriptive type. 16 managers of municipal elementary schools in the city of Bauru, São Paulo participated in the research. The instruments used were the script for observing the physical space and inclusive resources of the school context and the interview script for school managers. The results showed that the analysis in loco differs from the standpoint of the managers. However, both agree on the need to expand and improve the physical infrastructure, greater availability of material resources and adapted resources, principally in the common class.